Proposal of Marketing Strategy Gaharu Nusantara To Face market Competition in Year 2013 (The Indonesian Journal of Business Administration, 2013)
Gaharu Nusantara is a company that provides, manages and organizes some activities based on outdoor activity, such as outdoor gathering and outdoor training. Gaharu Nusantara has been trying to fulfill the companiesâ€™ needs of quality improvement for their employees. In 2012, Gaharu Nusantara faced tight competition in their business especially in price and products/services that were offered by the competitors. Moreover, based on data of sales performance Gaharu Nusantara from 2010 until 2012, Gaharu Nusantara now faces a problem which is affected to the income of Gaharu Nusantara, they cannot achieved the yearly target in 2012 and higher achievement target in 2013, fluctuated profit and sales due to its seasonal demand from their market, and hard to sell their products/services due to its intangibility factors. The research will implement an exploration of the industry situation analysis (external analysis), business situation analysis (internal analysis), segmentation, targeting, and positioning analysis, marketing mix analysis, SWOT analysis and conclude in the root cause analysis. From the analysis, it can be concluded that root causes of Gaharu Nusantara are lack of marketing and communication strategy and limited of target market and products. Therefore, this research would give a business solution for Gaharu Nusantara to win the market competition in year 2013. The proposed implementation plan for Gaharu Nusantara are how to communicate their products and services through Integrated Marketing Communication strategy in order to improve their promotion to the potential customers and the expanded of new target market and development of outdoor activity products in order to increase their salesÂ Keywords :Marketing Strategy, Outdoor Activity, Marketing Mix, SWOT Analysis